Tindak Tutur Ilokusi pada Podcast Bocor Alus Politik “Pusing Akibat Makan Siang Gratis” - Wida Minayanti; Muh Akbar Kurniawan (Mathematics Education Study Program, 2025)
Speech acts are defined as actions that regulate how to speak well. Illocutionary speech acts function to convey information or can also be used to do something. The purpose of this study is to identify the illocutionary speech contained in the podcast bocor alus politik “dizzy from free lunch”. The method used is descriptive qualitative. The data collection technique in this research uses listening and note taking. The source of data in this research is the video of the podcast bocor alus politics “dizzy due to free lunch”. The theory used is the study of pragmatics. This study uses illocutionary speech acts. The results of the speech act research on the podcast video bocor alus politics “dizzy from lunch” found as many as 14 assertive speech acts, 10 directive speech acts, 4 expressive speech acts, 3 commissive speech acts, and 2 declarative speech acts.